Texas blue [large type] - Thomas, Jodi (Thomas, Jodi. Whispering Mountain novel., 2011)
Determined to marry into a respectable family, gambler Lewton Paterson, sets his sights on Emily McMurray, one of the McMurray sisters. Unfortunately, Emily has no intention of ever getting married, especially to a man like Lewt.